Audit the Vision of your Institution - Gupta, B. L. (Journal of Engineering Education Transformations, 2008)
The vision statement indicates the future intents of the institution say after 10 years what it wants to achieve in terms of customer satisfaction. It is expressed in future expectations of the customers and employees. It sets the aspirations and ambitions of the employees.